Master batch, rubber composition for tire, tire, and production methods thereof
By mixing and curing cytotin nanofibers, colloidal siliconeica and diene-based rubber latex, a silicone rubber composite material with high dispersion was prepared, which solved the problems of low heat generation and insufficient shear resistance of existing tire materials, and improved tire fuel efficiency and shear resistance.
Patent Information
- Application Number
- JP2023145832
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Filing Date
- 2023-09-08
- Publication Date
- 2025-03-21
AI Technical Summary
Existing tire materials have shortcomings in low heat generation and shear resistance, making it difficult to simultaneously improve the fuel efficiency and shear resistance of the tire.
By mixing and curing the cytotin nanofiber dispersion, colloidal silicone and dienyl rubber latex, silicone rubber composite materials with high dispersion and high dispersion are prepared.
The low heat generation and shear resistance of silicone rubber composites are significantly improved, thereby improving the fuel efficiency and shear resistance of the tire.
Smart Images

Figure 2025039060000001
Abstract
Description
[Technical field]
[0001] The present invention relates to a masterbatch, a rubber composition for a tire, a tire, and methods for producing the same. [Background technology]
[0002] Cellulose fiber can be extracted from various biomass and has a small environmental impact, so various research and development efforts are being conducted on the use of cellulose fiber, including the use of cellulose fiber in pneumatic tires (see, for example, Patent Documents 1 to 3).
[0003] On the other hand, it is known to use silica, i.e., white carbon, as a filler in pneumatic tires. In pneumatic tires, wet silica is usually used in consideration of the balance between cost and performance.
[0004] Meanwhile, improvements in various performances such as fuel economy and cut resistance are required for pneumatic tires. In order to improve the fuel economy of pneumatic tires, it is effective to improve the low heat generation property of rubber. In order to improve the cut resistance of pneumatic tires, it is effective to improve the tear strength of rubber. [Prior art documents] [Patent documents]
[0005] [Patent Document 1] JP 2006-206864 A [Patent Document 2] JP 2009-191198 A [Patent Document 3] JP 2020-55962 A Summary of the Invention [Problem to be solved by the invention]
[0006] The present invention aims to provide a method for producing a masterbatch that is a raw material for vulcanized rubber that is excellent in low heat buildup and tear strength (i.e., cut resistance). In addition, the present invention aims to provide a method for producing a rubber composition that is a raw material for tires that are excellent in fuel efficiency and tear strength (i.e., cut resistance). The present invention also aims to provide a method for producing a tire that is excellent in fuel efficiency and tear strength (i.e., cut resistance). [Means for solving the problem]
[0007] The method for producing the masterbatch of the present invention comprises the steps of: A step of mixing at least a cellulose nanofiber dispersion, colloidal silica, and a diene-based rubber latex to prepare a mixed liquid; and solidifying the mixture.
[0008] The method for producing a masterbatch of the present invention involves the steps of mixing a cellulose nanofiber dispersion and a diene-based rubber latex and then coagulating the mixture, which allows the cellulose nanofibers to be dispersed to a higher degree than when the cellulose nanofibers are dried and then mixed with the diene-based rubber latex.
[0009] Moreover, since colloidal silica is mixed with the cellulose nanofiber dispersion and diene rubber latex, the dispersibility of the silica particles can be improved. This will be explained. Colloidal silica is a dispersion of silica particles. The silica particles in the colloidal silica are dispersed alone, that is, without agglomeration. According to the method for producing a masterbatch of the present invention, the colloidal silica is mixed with the cellulose nanofiber dispersion and diene rubber latex, and then the mixed liquid is coagulated, that is, the rubber particles, the cellulose nanofibers, and the non-aggregated silica particles are coagulated, so that not only the rubber particles but also the cellulose nanofibers can be inserted between the silica particles. Therefore, the aggregation of the silica particles can be reduced. In other words, the dispersibility of the silica particles can be improved.
[0010] Therefore, according to the method for producing a masterbatch of the present invention, it is possible to improve the low heat build-up and tear strength (that is, cut resistance) of vulcanized rubber.
[0011] The colloidal silica preferably has a particle size of 2 nm to 40 nm.
[0012] In the step of preparing the mixture, the amount of silica particles in the colloidal silica is preferably 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of the dry rubber content of the diene rubber latex.
[0013] The fiber diameter of the cellulose nanofibers in the cellulose nanofiber dispersion is preferably 100 nm or less.
[0014] In the step of preparing the mixture, the cellulose nanofibers in the cellulose nanofiber dispersion are preferably from 1 part by mass to 50 parts by mass per 100 parts by mass of the dry rubber content of the diene rubber latex.
[0015] The diene-based rubber latex is preferably a natural rubber latex.
[0016] The method for producing the rubber composition for tires of the present invention includes the steps of: preparing a master batch by the above-mentioned manufacturing method; and preparing a rubber composition using the masterbatch.
[0017] The method for producing a tire of the present invention includes the steps of: preparing a master batch by the above-mentioned manufacturing method; preparing a rubber composition using the masterbatch; and producing an unvulcanized tire using the rubber composition. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0018] Hereinafter, an embodiment of the present invention will be described.
[0019] <1. Manufacturing method of master batch> The method for producing the masterbatch of this embodiment includes at least a step of mixing a cellulose nanofiber dispersion, colloidal silica, and a diene-based rubber latex to prepare a mixed liquid (hereinafter, sometimes referred to as "step A"), and a step of solidifying the mixed liquid (hereinafter, sometimes referred to as "step B"). Since the method for producing the masterbatch of this embodiment includes steps A and B, it is possible to improve the low heat build-up and tear strength (i.e., cut resistance) of the vulcanized rubber. The method for producing the masterbatch of this embodiment can further include a step of dehydrating the solidified product (hereinafter, sometimes referred to as "step C"), if necessary.
[0020] <1.1. Step A (Preparation of Mixture)> In step A, at least the cellulose nanofiber dispersion, colloidal silica, and diene-based rubber latex are mixed to prepare a mixture. For this mixing, a dispersing machine such as a high-shear mixer, a homomixer, a ball mill, a bead mill, a high-pressure homogenizer, an ultrasonic homogenizer, or a colloid mill can be used.
[0021] The cellulose nanofiber dispersion may contain cellulose nanofibers and water. In the cellulose nanofiber dispersion, the cellulose nanofibers may be dispersed in water. The cellulose nanofiber dispersion may contain other additives, such as an organic solvent, a surfactant, and a dispersant, as necessary. Examples of the dispersant include an acrylic dispersant and an acrylamide dispersant. It is preferable that the cellulose nanofiber dispersion does not contain a dispersant. This can reduce costs.
[0022] Examples of raw materials for cellulose nanofibers include wood, rice husks, straw, bamboo, etc. When the raw material is pulp, cellulose nanofibers can be obtained, for example, by a method including a procedure of subjecting the pulp to chemical and / or enzymatic treatment and then defibrating it in water. Cellulose nanofibers can also be obtained by a method including a procedure of mechanically defibrating the pulp in water without chemical or enzymatic treatment.
[0023] When the cellulose nanofiber is produced by a method including a step of mechanically defibrating the pulp in water, the step is preferably a step of defibrating the pulp by the collision of at least two liquid flows containing the pulp. This can further improve the rigidity of the vulcanized rubber. This is thought to be because the pulp is defibrated by the collision of these liquid flows, which can suppress excessive pulverization, and as a result, can suppress the decrease in the reinforcing effect of the cellulose nanofiber that may occur due to excessive pulverization. An example of a cellulose nanofiber produced by such a step is "WFo-10002" manufactured by Sugino Machine Co., Ltd. (the cellulose nanofiber product used in the examples described below). The number of liquid flows may be two, three, or four or more. Incidentally, before or after the collision, i.e., the collision of at least two liquid flows, another liquid flow may further collide. This other liquid flow may be a pulp-containing liquid flow or a pulp-free liquid flow.
[0024] The fiber diameter of the cellulose nanofiber is preferably less than 1000 nm, more preferably 300 nm or less, even more preferably 100 nm or less, and even more preferably 70 nm or less. The fiber diameter of the cellulose nanofiber may be, for example, 2 nm or more, or 10 nm or more. The fiber diameter of the cellulose nanofiber may be the arithmetic mean of the fiber diameters of 10 randomly selected cellulose nanofibers. The fiber diameter of the cellulose nanofiber can be measured by a field emission scanning electron microscope, i.e., FE-SEM. For example, it can be measured by the following method.
[0025] (Method for measuring fiber diameter of cellulose nanofiber) The cellulose nanofiber dispersion is diluted with distilled water. The diluted solution is dropped onto a grid, dried, and the cellulose nanofibers are observed using a field emission scanning electron microscope (FE-SEM) under the following conditions. Observation magnification: 2000x Working distance WD=2mm Detector InLens Electron beam acceleration voltage: 1 kV The fiber diameter of the cellulose nanofibers shown in the FE-SEM image is measured.
[0026] The fiber length of the cellulose nanofiber is preferably 40 μm or less, more preferably 20 μm or less, and even more preferably 10 μm or less. By being 40 μm or less, it is possible to prevent the viscosity of the cellulose nanofiber dispersion or the mixed liquid from becoming excessively high, and therefore the cellulose nanofiber can be dispersed to a higher degree. The fiber length of the cellulose nanofiber may be, for example, 0.1 μm or more, 1 μm or more, or 2 μm or more. Here, "fiber length" means the length of at least one fiber in the cellulose nanofiber dispersion. The fiber length of the cellulose nanofiber can also be measured by a field emission scanning electron microscope, i.e., FE-SEM. For example, it can be measured by an FE-SEM image taken under the above-mentioned observation conditions.
[0027] In colloidal silica, silica particles are dispersed in a dispersion medium, such as water, an alcohol-based solvent, or a mixture thereof. Of these, it is preferable that the silica particles are dispersed in water. The silica particles in colloidal silica can be dispersed independently, that is, without agglomeration.
[0028] The particle size of colloidal silica, i.e., the particle size of silica particles in colloidal silica, is preferably 40 nm or less, more preferably 30 nm or less, and even more preferably 20 nm or less. If it is 40 nm or less, the low heat generation property and tear strength of vulcanized rubber can be further improved. The particle size of colloidal silica may be, for example, 2 nm or more, 4 nm or more, or 6 nm or more. The particle size of colloidal silica can be calculated based on the specific surface area and density obtained by the Sears method or the BET method.
[0029] The diene-based rubber latex is a rubber latex containing diene-based rubber particles (hereinafter, sometimes simply referred to as "rubber particles"). In the diene-based rubber latex, the diene-based rubber particles can be dispersed in a colloidal state in a dispersion medium. Specifically, in the diene-based rubber latex, the diene-based rubber particles can be dispersed in a colloidal state in water. The diene-based rubber latex may contain an organic solvent. That is, when the dispersion medium is water, the dispersion medium may contain an organic solvent. The diene-based rubber may have an unsaturated hydrocarbon bond, preferably a carbon-carbon double bond, in the main chain.
[0030] Examples of diene rubber latex include natural rubber latex and synthetic rubber latex, with natural rubber latex being preferred.
[0031] Examples of natural rubber latex include concentrated natural rubber latex and field latex. In natural rubber latex, rubber particles can be dispersed in a colloidal state in a dispersion medium. Specifically, in natural rubber latex, rubber particles can be dispersed in a colloidal state in water. Natural rubber latex may contain an organic solvent. That is, when the dispersion medium is water, the dispersion medium may contain an organic solvent.
[0032] The dry rubber content of the natural rubber latex is preferably 10% by mass or more, more preferably 20% by mass or more. The upper limit of the dry rubber content in the natural rubber latex is, for example, 60% by mass or 50% by mass.
[0033] A carbon black slurry may be mixed with the cellulose nanofiber dispersion, colloidal silica, and diene-based rubber latex.
[0034] The carbon black slurry may contain carbon black and water. In the carbon black slurry, carbon black may be dispersed in water. The carbon black slurry may be obtained by adding carbon black to water and stirring. For stirring, a dispersing machine such as a high shear mixer, homomixer, ball mill, bead mill, high pressure homogenizer, ultrasonic homogenizer, colloid mill, etc. may be used. The carbon black slurry may contain other additives such as an organic solvent and a surfactant, if necessary.
[0035] As the carbon black, for example, furnace black such as SAF, ISAF, HAF, FEF, GPF, etc., as well as conductive carbon black such as acetylene black and ketjen black, etc., can be used. The carbon black may be granulated carbon black, which is granulated in consideration of its handling properties, or may be ungranulated carbon black. One or more of these may be used.
[0036] With respect to the mixed liquid, the amount of the cellulose nanofibers (specifically, the cellulose nanofibers from the cellulose nanofiber dispersion) is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the dry rubber content of the diene rubber latex. The amount of the cellulose nanofibers may be, for example, 50 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less, per 100 parts by mass of the dry rubber content of the diene rubber latex.
[0037] Regarding the mixed liquid, the amount of silica particles (specifically, silica particles from colloidal silica) is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the dry rubber content of the diene rubber latex. The amount of silica particles may be, for example, 30 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less, per 100 parts by mass of the dry rubber content of the diene rubber latex.
[0038] Regarding the mixed liquid, the mass of cellulose nanofibers from the cellulose nanofiber dispersion (hereinafter referred to as "mass M C "), and the mass of silica particles from colloidal silica (hereinafter referred to as "mass M S ") with respect to mass M C and mass M S When the total is 100%, the mass M C may be, for example, 5% or more, 10% or more, or 20% or more. C may be, for example, 80% or less, 60% or less, 40% or less, or 30% or less.
[0039] <1.2. Step B (Step of solidifying the mixed liquid)> In step B, the mixed liquid is solidified. That is, the rubber particles, cellulose nanofibers, and silica particles in the mixed liquid are co-coagulated. When the mixed liquid contains carbon black, the carbon black can be co-coagulated together with these. In order to coagulate the mixed liquid, the mixed liquid may be heated and dried, pulse-dried, or a coagulant may be added to the mixed liquid. From the viewpoint of time and labor, heat drying and addition of a coagulant are preferable. An example of the coagulant is an acid. Examples of the acid include formic acid and sulfuric acid. The coagulant may be added while stirring the mixed liquid, while heating the mixed liquid, or in any combination of these (i.e., stirring and heating).
[0040] After coagulation, the coagulated material is separated from the waste liquid, if necessary. The coagulated material may be in the form of small pieces. The small pieces of the coagulated material are sometimes called crumbs. To separate the coagulated material from the waste liquid, for example, a filter may be used.
[0041] <1.3. Step C (dehydrating the coagulum)> The coagulated material is dehydrated as necessary. For example, an extruder, an oven, a vacuum dryer, or an air dryer can be used to dehydrate the coagulated material. Among these, an extruder is preferred. By using an extruder, the coagulated material can be dehydrated by the action of squeezing or the like, and the dehydrated coagulated material can be plasticized while being dried. An example of the extruder is a single-screw extruder.
[0042] <1.4. Other processes> The extruded coagulum, i.e., the dehydrated coagulum, is cut as necessary and compression molded into any shape (for example, a bale shape) as necessary. For cutting, for example, a pelletizer can be used.
[0043] The masterbatch thus obtained can be in the form of a bale. The masterbatch is not limited to a bale shape, and may be in the form of, for example, a pellet, a rod, or a sheet.
[0044] The masterbatch includes a rubber component including a diene rubber. The amount of the diene rubber in 100% by mass of the rubber component in the masterbatch can be, for example, 80% by mass or more, 90% by mass or more, or 100% by mass.
[0045] In the masterbatch, the amount of natural rubber in 100% by mass of diene rubber is preferably 80% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and still more preferably 100% by mass.
[0046] The master batch contains cellulose nanofibers. The amount of the cellulose nanofibers is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component. The amount of the cellulose nanofibers may be, for example, 50 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less.
[0047] The master batch contains silica particles. The amount of the silica particles is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component. The amount of the silica particles may be, for example, 30 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less.
[0048] The master batch may further include a compounding agent such as carbon black. The amount of carbon black is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, based on 100 parts by mass of the rubber component. The amount of carbon black may be, for example, 50 parts by mass or less, 30 parts by mass or less, or 20 parts by mass or less.
[0049] <2. Tire manufacturing method> The tire manufacturing method of the present embodiment includes the steps of preparing a master batch by the above-described method, preparing a rubber composition using the master batch, and preparing an unvulcanized tire using the rubber composition.
[0050] <2.1. Step of preparing rubber composition using masterbatch> This process (specifically, the process of preparing a rubber composition using the masterbatch) can include kneading at least the masterbatch and compounding ingredients to prepare a rubber mixture, and kneading at least the rubber mixture and vulcanization-based compounding ingredients to obtain the rubber composition.
[0051] In this step, at least the master batch and compounding agents are kneaded to prepare a rubber mixture. Examples of compounding agents include fillers, zinc oxide, stearic acid, wax, antioxidants, silane coupling agents, and vulcanization compounding agents. Compounding agents can be selected from these, or any combination thereof. However, it is preferable not to add vulcanization compounding agents at this stage. Examples of fillers include carbon black, silica, clay, talc, calcium carbonate, magnesium carbonate, and aluminum hydroxide. Filling agents can be selected from these, or any combination thereof. When carbon black is added at this stage, the characteristics of the carbon black may be the same as or different from the characteristics of the carbon black used in the carbon black slurry. For example, the grade of carbon black added at this stage may be the same as or different from the grade of carbon black used in the carbon black slurry according to ASTM (American Society for Testing and Materials). Examples of the antiaging agent include aromatic amine-based antiaging agents, amine-ketone-based antiaging agents, monophenol-based antiaging agents, bisphenol-based antiaging agents, polyphenol-based antiaging agents, dithiocarbamate-based antiaging agents, and thiourea-based antiaging agents. The antiaging agent can be selected from these, either alone or in any combination. Other rubbers may be kneaded together with the master batch and compounding agents. Examples of such rubbers include natural rubber, polyisoprene rubber, butadiene rubber, styrene-butadiene rubber, nitrile rubber, and chloroprene rubber. Examples of the antiaging agent can include one or in any combination. The kneading can be performed with a kneader. Examples of the kneader include an internal kneader and an open roll. Examples of the internal kneader include a Banbury mixer and a kneader.
[0052] In this step, at least the rubber mixture and the vulcanization compounding agents are kneaded to obtain a rubber composition. Examples of the vulcanization compounding agents include sulfur, organic peroxides and other vulcanizing agents, vulcanization accelerators, vulcanization accelerator assistants, and vulcanization retarders. The vulcanization compounding agents can be selected from these, or any combination thereof. Examples of sulfur include powdered sulfur, precipitated sulfur, insoluble sulfur, and highly dispersible sulfur. The sulfur can be selected from these, or any combination thereof. Examples of the vulcanization accelerator include sulfenamide-based vulcanization accelerators, thiuram-based vulcanization accelerators, thiazole-based vulcanization accelerators, thiourea-based vulcanization accelerators, guanidine-based vulcanization accelerators, and dithiocarbamate-based vulcanization accelerators. The vulcanization accelerator can be selected from these, or any combination thereof. The kneading can be performed with a kneading machine. Examples of the kneading machine include an internal kneading machine and an open roll. Examples of the internal kneading machine include a Banbury mixer and a kneader.
[0053] The rubber composition includes a rubber component derived from the master batch. The amount of the rubber component derived from the master batch can be, for example, 20% by mass or more, 40% by mass or more, 60% by mass or more, 80% by mass or more, or 100% by mass, based on 100% by mass of the rubber component in the rubber composition.
[0054] In the rubber composition, the amount of natural rubber is preferably 40% by mass or more, more preferably 60% by mass or more, and even more preferably 70% by mass or more, based on 100% by mass of the rubber component. The amount of natural rubber may be 80% by mass or more, 90% by mass or more, or may be 100% by mass.
[0055] In 100% by mass of the rubber component in the rubber composition, the amount of the butadiene rubber may be, for example, 5% by mass or more, 10% by mass or more, or 20% by mass or more. The amount of the butadiene rubber may be, for example, 60% by mass or less, 40% by mass or less, or 30% by mass or less.
[0056] The rubber composition contains cellulose nanofibers. The amount of the cellulose nanofibers is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component in the rubber composition. The amount of the cellulose nanofibers may be, for example, 50 parts by mass or less, 30 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less.
[0057] The rubber composition contains silica particles. The amount of the silica particles is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component in the rubber composition. The amount of the silica particles may be, for example, 30 parts by mass or less, 20 parts by mass or less, or 15 parts by mass or less.
[0058] The rubber composition may contain carbon black. The amount of carbon black is preferably 1 part by mass or more, more preferably 3 parts by mass or more, and even more preferably 5 parts by mass or more, per 100 parts by mass of the rubber component in the rubber composition. The amount of carbon black may be, for example, 50 parts by mass or less, 30 parts by mass or less, or 20 parts by mass or less.
[0059] The total amount of the cellulose nanofibers, silica particles, and carbon black is preferably 6 parts by mass or more, more preferably 15 parts by mass or more, and even more preferably 20 parts by mass or more, per 100 parts by mass of the rubber component in the rubber composition. This total amount may be, for example, 80 parts by mass or less, 50 parts by mass or less, or 40 parts by mass or less.
[0060] The rubber composition may further include zinc oxide, stearic acid, wax, antioxidant, silane coupling agent, sulfur, vulcanization accelerator, etc. The rubber composition may include one or any combination of these. The amount of sulfur is preferably 0.5 to 5 parts by mass in terms of sulfur content per 100 parts by mass of the rubber component in the rubber composition. The amount of vulcanization accelerator is preferably 0.1 to 5 parts by mass per 100 parts by mass of the rubber component in the rubber composition.
[0061] The rubber composition can be used to manufacture tires. Specifically, the rubber composition can be used to manufacture tire components that constitute tires. For example, the rubber composition can be used to manufacture tread rubber, sidewall rubber, chafer rubber, bead filler rubber, etc. The rubber composition can be used to manufacture one or any combination of these tire components.
[0062] <2.2. Step of producing unvulcanized tire using rubber composition> The tire manufacturing method of the present embodiment includes a step of producing an unvulcanized tire using the rubber composition. This step may include producing a tire component including the rubber composition, and producing an unvulcanized tire including the tire component. Examples of the tire component include tread rubber, sidewall rubber, chafer rubber, and bead filler rubber. Among them, sidewall rubber is preferable.
[0063] <2.3. Other processes> The tire manufacturing method of the present embodiment may further include a step of vulcanizing and molding the unvulcanized tire. The tire obtained by the method of the present embodiment may be a pneumatic tire.
[0064] <3. Various modifications can be made to the above-described embodiment> The above-described embodiment may be modified in various ways. For example, the above-described embodiment may be modified by selecting one or more of the following modifications.
[0065] In the above embodiment, the configuration in which water is used to prepare the carbon black slurry has been described. However, the above embodiment is not limited to this configuration. For example, dilute rubber latex may be used instead of water. Specifically, the carbon black slurry may be prepared by adding carbon black to the dilute rubber latex and stirring the mixture. In the dilute rubber latex, rubber particles may be dispersed in water in a colloidal state. The water may be water containing an organic solvent, for example. The dry rubber content of the dilute rubber latex is preferably 0.1% by mass or more, more preferably 0.3% by mass or more. The upper limit of the dry rubber content is preferably 5% by mass, more preferably 2% by mass. The dilute rubber latex may be prepared by, for example, diluting natural rubber latex with water. Synthetic rubber latex may be used instead of natural rubber latex.
[0066] In the above embodiment, the master batch and the compounding ingredients are kneaded to prepare the rubber mixture. However, the above embodiment is not limited to this configuration. For example, the rubber mixture may be treated as the master batch.
[0067] In the above embodiment, the tire is a pneumatic tire. However, the above embodiment is not limited to this configuration. EXAMPLES
[0068] The following describes an embodiment of the present invention.
[0069] The raw materials and chemicals used in the examples are as follows. Natural rubber latex "NR Field Latex" manufactured by Golden Hope Solid natural rubber "NR Field Latex" solid rubber made by drying Golden Hope Co. Butadiene rubber "BR150B" manufactured by Ube Industries CNF1 "WFo-10002" manufactured by Sugino Machine Co., Ltd. Aqueous dispersion of cellulose nanofibers with a fiber diameter of 10 to 50 nm and a fiber length of 1 to 9 μm (Note that the fiber diameter and fiber length are catalog values.) CNF2 "Extra long product" manufactured by Sugino Machine Co., Ltd. Aqueous dispersion of cellulose nanofibers with a fiber diameter of 10 to 60 nm and a fiber length of 5 to 9 μm (Note that the fiber diameter and fiber length are catalog values.) Wet silica "Ultrasil VN3" manufactured by EVONIK Colloidal silica 1 "Snowtex (registered trademark) XS" manufactured by Nissan Chemical Industries, Ltd. (aqueous dispersion of silica particles with a diameter of 4 to 6 nm) Colloidal silica 2 "Snowtex (registered trademark) 30" manufactured by Nissan Chemical Industries, Ltd. (aqueous dispersion of silica particles with a diameter of 10 to 15 nm) Carbon black "Diablack A" manufactured by Mitsubishi Chemical Corporation Zinc oxide "Zinc oxide type 2" manufactured by Mitsui Mining & Smelting Co., Ltd. Stearic acid "Stearic acid" manufactured by NOF Corporation Anti-aging agent "Santoflex 6PPD" manufactured by Flexis Sulfur "Oil treatment 150 mesh powder sulfur" manufactured by Tsurumi Chemical Industry Co., Ltd. Vulcanization accelerator "Suncerer NS-G" manufactured by Sanshin Chemical Industry Co., Ltd.
[0070] Preparation of masterbatches in Examples 1 to 9 Natural rubber latex and colloidal silica were added to the cellulose nanofiber dispersion according to the formulation shown in Table 1, and the mixture was stirred at 1000 rpm for 30 minutes in a mixer (Super Mixer SM-20, Kawata Corporation) to obtain a mixture. The mixture was placed in an oven and dried overnight at 70°C. A master batch was obtained by this procedure.
[0071] Preparation of Masterbatch in Comparative Example 3 Natural rubber latex and wet silica were added to the cellulose nanofiber dispersion according to the formulation shown in Table 1, and the mixture was stirred at 1000 rpm for 30 minutes in a mixer (Super Mixer SM-20, Kawata Corporation) to obtain a mixture. The mixture was placed in an oven and dried overnight at 70°C. A master batch was obtained by this procedure.
[0072] Preparation of Masterbatches in Comparative Examples 4 and 5 Colloidal silica was added to natural rubber latex according to the formula shown in Table 1, and the mixture was stirred at 1000 rpm for 30 minutes in a mixer (Super Mixer SM-20, manufactured by Kawata Corporation) to obtain a mixed liquid. The mixed liquid was placed in an oven and dried overnight at 70°C. A master batch was obtained by this procedure.
[0073] Preparation of Masterbatches in Comparative Examples 6 and 7 Natural rubber latex was added to the cellulose nanofiber dispersion according to the formula shown in Table 1, and the mixture was stirred at 1000 rpm for 30 minutes using a mixer (Super Mixer SM-20, manufactured by Kawata Corporation) to obtain a mixture. The mixture was placed in an oven and dried overnight at 70°C. A master batch was obtained using this procedure.
[0074] Preparation of unvulcanized rubber in Examples 1 to 9 and Comparative Examples 3 to 7 The compounding ingredients except for sulfur and vulcanization accelerator were added to the master batch according to Table 1, and kneaded in a Banbury mixer to obtain a rubber mixture. The rubber mixture, sulfur, and vulcanization accelerator were kneaded in a Banbury mixer to obtain an unvulcanized rubber.
[0075] Preparation of Unvulcanized Rubber in Comparative Examples 1 and 2 The compounding ingredients except for sulfur and vulcanization accelerator were added to solid natural rubber according to Table 1, and kneaded in a Banbury mixer to obtain a rubber mixture. The rubber mixture, sulfur, and vulcanization accelerator were kneaded in a Banbury mixer to obtain unvulcanized rubber. In Comparative Examples 1 and 2, the cellulose nanofiber dispersion was dried before being added to the solid natural rubber (i.e., the dry powder of cellulose nanofiber was added to the solid natural rubber). In Comparative Example 2, the colloidal silica was dried before being added to the solid natural rubber.
[0076] Preparation of vulcanized rubber in each example The unvulcanized rubber was vulcanized at 150°C for 30 minutes to obtain a vulcanized rubber.
[0077] Cut resistance The tear strength was measured in accordance with JIS K6252-1:2015. Specifically, a crescent-shaped test piece was prepared using vulcanized rubber, specifically, a crescent-shaped test piece with a 0.50±0.08 mm cut in the center of the indentation was made, and the crescent-shaped test piece was pulled at a tensile speed of 500 mm / min using a tensile tester manufactured by Shimadzu Corporation until it broke. The maximum force required to tear the crescent-shaped test piece was divided by the thickness of the crescent-shaped test piece. This gave the tear strength. The tear strength of each example is shown in Table 1 as an index with the tear strength of Comparative Example 1 taken as 100. The larger the index, the higher the tear strength and the better the cut resistance.
[0078] Fever The tan δ of the vulcanized rubber was measured using a viscoelasticity tester manufactured by Toyo Seiki Seisakusho. The measurement conditions were static strain 10%, dynamic strain ±2%, frequency 50Hz, and temperature 60°C. The tan δ of each example is shown in Table 1 as an index, with the tan δ of Comparative Example 1 set at 100. The smaller the index, the lower the tan δ, and the less likely it is to generate heat, and therefore the more excellent the fuel economy.
[0079] [Table 1] In this table, the amounts of CNF1 and CNF2 represent the net amount of cellulose nanofibers, not the amount of cellulose nanofiber dispersion, and the amount of colloidal silica represents the net amount of silica, not the amount of dispersion.
[0080] When natural rubber latex and colloidal silica were added to the cellulose nanofiber dispersion and then stirred, the low heat generation and cut resistance were superior compared to when only natural rubber latex was added to the cellulose nanofiber dispersion and then stirred (see Comparative Example 6 and Example 3).
[0081] When natural rubber latex and colloidal silica were added to a cellulose nanofiber dispersion and then stirred, the low heat generation and cut resistance were superior to those when only colloidal silica was added to natural rubber latex and then stirred (see Comparative Example 5 and Example 3).
[0082] When natural rubber latex and colloidal silica were added to the cellulose nanofiber dispersion and then stirred, the low heat generation and cut resistance were superior to when natural rubber latex and wet silica were added to the cellulose nanofiber dispersion and then stirred (see Comparative Example 3 and Example 3).
Claims
1. A step of mixing at least a cellulose nanofiber dispersion, colloidal silica, and a diene-based rubber latex to prepare a mixed liquid; and solidifying the mixture. The manufacturing method of the masterbatch.
2. The method for producing a masterbatch according to claim 1, wherein the colloidal silica has a particle size of 2 nm to 40 nm.
3. 2. The method for producing a masterbatch according to claim 1, wherein in the step of preparing the mixed liquid, an amount of silica particles in the colloidal silica is 1 part by mass or more and 30 parts by mass or less per 100 parts by mass of a dry rubber content of the diene rubber latex.
4. The method for producing a masterbatch according to claim 1 , wherein the fiber diameter of the cellulose nanofibers in the cellulose nanofiber dispersion is 100 nm or less.
5. 2. The method for producing a masterbatch according to claim 1, wherein in the step of preparing the mixed liquid, the cellulose nanofibers in the cellulose nanofiber dispersion are present in an amount of 1 part by mass or more and 50 parts by mass or less per 100 parts by mass of a dry rubber content of the diene rubber latex.
6. The method for producing a masterbatch according to claim 1 , wherein the diene-based rubber latex is a natural rubber latex.
7. A step of producing a masterbatch by the method for producing a masterbatch according to any one of claims 1 to 6; and preparing a rubber composition using the master batch. A method for producing a rubber composition for tires.
8. A step of producing a masterbatch by the method for producing a masterbatch according to any one of claims 1 to 6; preparing a rubber composition using the masterbatch; and producing an unvulcanized tire using the rubber composition. A method for manufacturing tires.
Citation Information
Patent Citations
Masterbatch of rubber / short fiber, manufacturing method for the same and pneumatic tire using the same
JP2006206864A
Rubber composition and method for producing the same
JP2009191198A
Method for producing rubber wet master batch
JP2020055962A